TEACHERS' UNDERSTANDING AND PRACTICES IN ASSESSING HIGHER ORDER THINKING SKILLS AT PRIMARY SCHOOLS - Elin Driana; Ernawati Ernawati (Universitas Muhammadiyah Kalimantan Timur, 2019)
The aim of this research was to explore primary school teachers’ understanding about higher order thinking skills (HOTS), its implementation in classroom assessments, and the quality of the HOTS assessment instrument constructed by the teachers. This qualitative research that was conducted from August to December 2018 involved 10 public and private primary school teachers in Jakarta and it is surrounding areas. Data about the teachers’ understanding of HOTS and how teachers applied the assessment of HOTS were obtained through semi-structured interviews. Meanwhile, the quality of the HOTS assessment instrument constructed by the teachers was analyzed to assess its alignment with basic competencies which have become the purpose of learning and the revised Bloom’s taxonomy to determine the level of cognitive process in each item. The research results showed that the primary school teachers that participated in this research have not had a comprehensive understanding of HOTS. The majority of the HOTS items that they made were still limited to analysis in the form of multiple choice items. There were also misunderstandings about the HOTS items. In general, the HOTS instrument constructed by the primary school teachers had good content validity, but there was a difference regarding the cognitive process involved in the items the between the perception of the teachers and the perception of the expert. Teachers had the tendency to perceive the items that they have made as HOTS items, although those items were categorized as remembering and understanding. This difference in perception occurred because the teachers did not have a comprehensive understanding of HOTS yet.